2023
DOI: 10.1186/s12951-023-01985-1
|View full text |Cite|
|
Sign up to set email alerts
|

Cold exposure protects against medial arterial calcification development via autophagy

Abstract: Medial arterial calcification (MAC), a systemic vascular disease different from atherosclerosis, is associated with an increased incidence of cardiovascular events. Several studies have demonstrated that ambient temperature is one of the most important factors affecting cardiovascular events. However, there has been limited research on the effect of different ambient temperatures on MAC. In the present study, we showed that cold temperature exposure (CT) in mice slowed down the formation of vitamin D (VD)-indu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Another signi cant nding from our study is the observed increase in levels of hsa-miR-320a-3p, which plays a pivotal role in regulating the AMPK/mTOR autophagy pathway [32]. Vanderplow et al's work sheds light on how any downturn in Akt-mTOR signaling can dent the synaptic structural and functional plasticity in the prefrontal cortex (PFC), ultimately affecting PFC-mediated cognition in patients with BD [33].…”
Section: Discussionmentioning
confidence: 60%
“…Another signi cant nding from our study is the observed increase in levels of hsa-miR-320a-3p, which plays a pivotal role in regulating the AMPK/mTOR autophagy pathway [32]. Vanderplow et al's work sheds light on how any downturn in Akt-mTOR signaling can dent the synaptic structural and functional plasticity in the prefrontal cortex (PFC), ultimately affecting PFC-mediated cognition in patients with BD [33].…”
Section: Discussionmentioning
confidence: 60%
“…Wang et al reported that miR-320a accelerated the proliferation of myocardial fibroblasts by regulating the mTOR signaling pathway in HEH2 cells [ 27 ]. Li et al claimed that miR-320a-3p prevented the development of medial arterial calcification through the AMPK/mTOR autophagy pathway [ 28 ]. After searching the published literature, we did find that miR-320a-3p is associated with predicted target genes and associated signaling pathways in animal or cellular models.…”
Section: Discussionmentioning
confidence: 99%